Relationship Between Position and Work Duration with Suspect Carpal Tunnel Syndrome in Maxim Online motorcycle taxi at Makassar (Nusantara Medical Science Journal, 2023)
Introduction:   Online motorcycle taxi is a service that is currently widely used in goods delivery services and other forms of services. There are several things that are not considered by online motorcycle taxi drivers when driving, namely the driving position that is not good and correct. The more consumer demand for online motorcycle taxi applications, the higher the working hours of online motorcycle taxi drivers which leads to increased complaints of pain in the body. This study aims to determine the relationship between position and duration of work with complaints of suspected carpal tunnel syndrome in maxim motorcycle taxi drivers in Makassar City. Methods: The sampling technique in this study was purposive sampling through a cross sectional approach. Respondents in this study were riders aged 17 years and over as many as 373 riders who met the exclusion and inclusion criteria. Work position was measured using REBA, Work Duration was measured using a work duration questionnaire, while Suspect carpal tunnel syndrome complaints were measured using Phalen's Test. Results: The Kolmogorov Smirnov normality test shows a significance value (p) of 0.000, meaning that the data is not normally distributed (p